Sentiment investor, catering incentives, corruption, COVID-19, and dividend policy - Shindy Dwita Nuansari; Eduardus Tandelilin; Nur Hayatiningsih; Dhiyan Septa Wihara; Sigit Ratnanto; Silvia Waning Hiyun Puspita Sari (Universitas Negeri Surabaya, Indonesia, 2026)
This study examines how corporate dividend policies are shaped by investor sentiment and behavioral factors through dividend catering theory during the COVID-19 period. Using panel data from 31 countries over 2018–2022, this study applies a quantitative approach with the SYS-GMM estimation method. The results show that catering incentives positively affect dividends in low investor sentiment conditions but negatively in high sentiment conditions. This effect becomes stronger during the COVID-19 pandemic, particularly when sentiment is low. In addition, corruption levels amplify the impact of catering incentives on dividend policy depending on investor sentiment. This study contributes by highlighting the interaction between investor sentiment, crisis conditions, and institutional environment in determining dividend decisions, offering insights for firms seeking to maintain value under changing market conditions.